2010
DOI: 10.1158/1541-7786.mcr-10-0302
|View full text |Cite
|
Sign up to set email alerts
|

GD3 Synthase Expression Enhances Proliferation and Tumor Growth of MDA-MB-231 Breast Cancer Cells through c-Met Activation

Abstract: The disialoganglioside G D3 is overexpressed in ∼50% of invasive ductal breast carcinoma, and the G D3 synthase gene (ST8SIA1) displays higher expression among estrogen receptor-negative breast cancer tumors, associated with a decreased overall survival of breast cancer patients. However, no relationship between ganglioside expression and breast cancer development and aggressiveness has been reported. We have previously shown that overexpression of G D3 synthase induces the accumulation of b-and c-series gangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 49 publications
4
63
1
2
Order By: Relevance
“…Recently, clinical studies showed that high expression of GD3S was found in estrogen receptor (ER)-negative breast cancer and was associated with poor histological grade in ER-negative tumors (29). GD3S can enhance proliferation of MDA-MB-231 breast cancer cells through the constitutive activation of the c-MET receptor and downstream mitogen-activated protein kinase/extracellular signal-regulated kinase and phosphoinositide-3 kinase/Akt signaling pathways (35). With respect to breast CSCs, GD3S not only regulates epithelial-mesenchymal transition and CSC properties but also metastasis in vivo (46).…”
Section: Gd3 Antibody Mediates Cdc Against Gbm Cells and Suppressesmentioning
confidence: 99%
“…Recently, clinical studies showed that high expression of GD3S was found in estrogen receptor (ER)-negative breast cancer and was associated with poor histological grade in ER-negative tumors (29). GD3S can enhance proliferation of MDA-MB-231 breast cancer cells through the constitutive activation of the c-MET receptor and downstream mitogen-activated protein kinase/extracellular signal-regulated kinase and phosphoinositide-3 kinase/Akt signaling pathways (35). With respect to breast CSCs, GD3S not only regulates epithelial-mesenchymal transition and CSC properties but also metastasis in vivo (46).…”
Section: Gd3 Antibody Mediates Cdc Against Gbm Cells and Suppressesmentioning
confidence: 99%
“…Cazet et al reported that over-expression of the GD3 synthase in a clone of breast cancer cell line MDA-MB-231 was correlated with high proliferation rate in the absence of serum or exogenous growth factors, activation of c-MET that was independent of HGF-binding, activation of PI3K/ AKT and ERK signaling, and tumor growth in a SCID mouse model [52]. Moreover, the anti-GD2 4G2 mAbtreatment of the cells reduced their viability and this was correlated with decreased phosphorylation of c-MET.…”
Section: Analysis Of Signaling Pathways Induced By Targeting Of Ganglmentioning
confidence: 99%
“…16.3 ) (Basu et al 2004a ) occurs in those cell lines at much higher concentrations (50-150 m M) (Boyle et al 2006 ) by EBRAP followed by activation of caspase-8 ( Fig. 16.3 ) Several new chemicals have been tested in recent years for induction of the apoptotic process by activating IMCAP (internal mitochondrial caspase activating pathway), NF-kappaB (NFKBAP), EBRAP (external Bad-receptor activating pathway), or CPKAP pathway (Yuan et al 2011 ;Leung et al 2011 ;Ullah et al 2011 ;Marchetti et al 2011 ;Kim et al 2010 ;Laezza et al 2010 ;Wesierska et al 2011 ;Chou et al 2010 ;Zhang et al 2010 ;Patil et al 2010 ;Banerjee et al 2010 ;Shirure et al 2011 ;Cazet et al 2010 ) . We also tested activation of apoptosis via all other pathways given in Table 16.1 in the above mentioned cell lines using those apoptotic agents ( Fig.…”
Section: Induction Of Apoptosis In Breast Cancer Cells By Novel Agentsmentioning
confidence: 99%
“…Targeting mitochondria as a cancer therapeutic strategy is of interest in recent years. Besides recognition of inhibitors of GSL biosynthesis ( l -PPMP, d -PPMNP, and d -PDMP) and DNA biosynthesis (cisplatin) in our laboratory (Basu et al 2004a, b, c ;Ma et al 2004 ;Boyle et al 2006 ) several other different chemicals have been tested as apoptosis inducing agents (via intrinsic mitochondrial or extrinsic receptor pathways) in breast cancer cells Patil et al 2010 ;Banerjee et al 2010Banerjee et al , 2011Shirure et al 2011 ;Cazet et al 2010 ;Jada et al 2008 ;Domingo-Domenech et al 2008 ;Nakagawa et al 2007 ;Nakajima et al 2007 ;Sato-Cerrato et al 2005 ;Balabhadrapatharuni et al 2005 ;Hatasukari et al 2003 ;Chung et al 2002 ;Hansen et al 2000 ;Fromigue et al 2003 ;Elton et al 2000 ;Distefano et al 1998 ;Han et al 1998 ;Schwartz et al 1997 ;Sarkar et al 2007 ;Singh et al 2009 ;Lu et al 2006 ;Somers-Edgar and Rosegren 2009 ;Neuzil et al 2007 ;Fulda et al 1997 ;Li et al 2010a ;Chaouki et al 2010 a;Mullauer et al 2011a ;Kessler et al 2007a ;Laszczyk 2009 ;Bzesk et al 2006a ;Goldoni et al 2008 a;Ellerby et al 1999 ) .…”
Section: Apoptotic Agents As a New Generation Of Anticancer Drugsmentioning
confidence: 99%